Alat Musik Tradisional Di Masa Modern (Sape’ Dayak Kayaan Dalam Kajian Nilai Budaya) - Cornelius Kiki Hartanto; Diaz Restu Darmawan; Cristo Rodento Manalu; Ackenesiana Lenny (Gondang: Jurnal Seni dan Budaya, 2021)
The unity of harmony which forms the strains leads people to consider music as a means to lead, enliven entertainment as well as certain ritual ceremonies. Music that is increasingly developing turns into a tool that regulates relations between human relationships, life and its environment. In Indonesia, music is categorized into two types, namely traditional music (archipelago music) and modern music. These to types of music have different types of genre. However, nowadays, they have been packed a lot in combined ways. Traditional music consists of rhythm adaptation and tools that develop in a particular culture, so that, in this case, the presence of traditional music is lifted from everyday life which forms a certain characteristic for a culture. One of them is traditional musical instrument. An ethnic group named Dayak Kayaan who is located in Datah Dian village, Kapuas Hulu Regency, West Kalimantan, also has a traditional musical instrument.  The instrument is known as Sape'.  The method used in this study was qualitative research method with ethnographic approach. This approach was used to see how the people of Dayak Kayaan in Datah Dian village played and produced Sape’. In line with the development of modern music, Sape' music also flows with developments, its various functions divide the types of Sape'. These include the Kayaan Traditional Sape' music which functions as ritual and traditional ceremonies and Modern Sape' music which is played only for personal use.